Absence of bony patella in the white-eared opossum (Didelphis albiventris): Morphology and diagnostic imaging - Inamassu, L. R. [UNESP]; Mamprim, M. J. [UNESP]; Dadalto, C. R. [UNESP]; Cavaletti, F. C.; Mello, M. C.; Schimming, B. C. [UNESP] (Wiley, 2017)
Patella, the kneecap, is the best known and largest of the sesamoid bones and is present in the quadriceps femoris tendon. Typical patella appears in all extant mammals, with the exception of some marsupials and bats. No description about the white-eared opossum stifle was found in the available literature up to now. Thus, the knee joints of 16 Didelphis albiventris were examined by gross anatomy, histology, radiography and computed tomography images to determine the presence or absence of ossified patella in this animal. The most remarkable observation in white-eared opossum is the absence of a bony patella. The femoral trochlea is shallow, and the lateral gastrocnemius sesamoids are shown up in all opossums. The quadriceps femoris tendon is composed mainly of dense regular connective tissue with a classic fibrocartilage pad on the superficial surface of the tendon. The absence of a true patella seems to be typical for marsupials.